Evaluasi Permainan Tim RRQ Hoshi Pada MPL Season 14 (Studi Kasus Rotasi Permainan Tim RRQ Hoshi) - Revio Harkel; Feby Elra Perdima; Roni Syaputra (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to analyze RRQ Hoshi's rotations across 16 matches in the MPL Indonesia Season 14 Playoffs and Grand Finals, using descriptive qualitative methods with a case study approach. Data were collected through non-participant observation of video recordings to identify rotation patterns and effectiveness. The results show that RRQ Hoshi's rotations are highly inconsistent; at their best, their rotations are highly effective, coordinated, and proactive in securing crucial objectives like Turtle and Lord, which are key to victory. However, when performance declines, their rotations become chaotic, undisciplined, and often lead to fatal failures due to uncoordinated, high-risk aggression and an inability to compete for objectives under pressure. Therefore, it is concluded that RRQ's success is not determined by their proven rotation strategy, but rather by the consistency of their execution and team coordination, which are the fundamental factors that determine their victory or defeat.